Obowiązek zwrotu korzyści majątkowej uzyskanej z przestępstwa popełnionego przez inną osobę - Czwojda, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article deals with the evolution of legal regulations regarding the reimbursement of proceeds from crime by a person other than the perpetrator. The author analyses the premises for applying the principle of forfeiture of proceeds and chances relating to them, paying particular attention to the nature of Article 52 of the Criminal Code. The analysis also takes into account the positive direction of the changes and contains critical remarks concerning some solutions. The conclusion indicates a need for eliminating regulatory shortcomings, thus making it possible for the principle of forfeiture of proceeds to be a rational instrument of penal policy.
Keywords: proceeds; criminal liability under Article 52 of the Criminal Code; forfeiture of proceeds; reimbursement